2019
DOI: 10.3991/ijet.v14i07.9128
|View full text |Cite
|
Sign up to set email alerts
|

Digital Backchannel: Promoting Students' Engagement in EFL Large Class

Abstract: Students’ engagement is widely believed to be the single most significant predictor of persistence in learning process. It is generally reflected in active participation such as listening to presentation, expressing opinions, asking questions, and working on assignment. However, the idea of being embarrassed in front of peers and the feeling of being reluctant to disturb others can often be intimidating for many students and might prevent them to ask questions during class discussion. As the consequence, meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
2
8
0
1
Order By: Relevance
“…An implementation of online backchannel (as a formative assessment) in English writing classrooms had proven a beneficial way for students' writing process. It was in line with what the previous studies had claimed that using online discussion increased the students' engagement (Harunasari & Halim, 2019) and writing skills improvement (Jumariati & Febriyanti, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An implementation of online backchannel (as a formative assessment) in English writing classrooms had proven a beneficial way for students' writing process. It was in line with what the previous studies had claimed that using online discussion increased the students' engagement (Harunasari & Halim, 2019) and writing skills improvement (Jumariati & Febriyanti, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…As previous studies mentioned, online backchannel provides benefits to encourage the students' curiosity and interaction for students, especially for higher-level students. A study showed that backchannel was supposed to give engagement between students and their learning (Harunasari & Halim, 2019;Kassner & Cassada, 2017). They already stated that students could use backchannels as a device to engage them with their learning.…”
mentioning
confidence: 99%
“…They engage marginalized shy and introverted students by providing a more comfortable mode of communication that is a less threatening way to present ideas (Camiel et al, 2014;Carpenter, 2015;Krishnan & Poleon, 2013;Toledo & Peters, 2010). A digital backchannel chat platform has been shown to promote students' engagement in large English as a Foreign Language (EFL) classes by transferring the side conversation to the forefront (Harunasari & Halim, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They used these systems as secondary notification channels by which their friends in the group could request an immediate and private comment on their posted homework message, which has been shown to increase engagement in language classes (Harunasari & Halim, 2019). This desire for more notification of any updates to their group comments suggests that these third-party sites were increasing the quantity and quality of the collaborative experiences by reducing the delay between responses allowing more time to think (Toledo & Peters, 2010).…”
Section: Ilic Digital Backchannels In Collaborative Learningmentioning
confidence: 99%
“…Accepting or resisting online learning refers to students' perceptions toward usefulness and easiness influencing users' attitudes, intentions and actual behavior to use new technology (Ngampornchai & Adams, 2016). However, either the acceptance or resistance can never be valid without students' engagement which is unarguable the only critical predictor of a sustainable learning process (Harunasari & Halim, 2019).…”
Section: Introductionmentioning
confidence: 99%